From the Holy Alliance to Putin: Two centuries of Russia’s search for hegemony - Alcalde Cardoza, Javier (2015)
Russia’s current international behavior can be better understood by examining its main historical tendencies. Russia becomes military dominant power in Europe in 1812 and with the Holy Alliance attempts briefly to attain a hegemonic leadership, including preeminence in the field of ideas. After the Crimean War and the Great Game, played against Britain, Russia attempts again to attain hegemony with the Bolshevik Revolution and later in the Cold War. As a resurgent power, under Putin, she strives to attain a regional hegemony in the realm of Eurasia.